The Pistoia Alliance Controlled Substance Compliance Service Project: from start to finish. Issue 2 (February 2015) - Taylor, Daniel; Bowden, Stuart G.; Knorr, Reinhard; Wilson, Derek R.; Proudfoot, John; Dunlop, Anne E.
Highlights Controlled substances are covered by rapidly evolving legislation. Legislation must be translated from into chemical structures. A cross-industry team has defined a new controlled substance service. We discuss the use of chemoinformatics to decide if a substance is controlled. We highlight the impact of different legislative approaches between countries.